2017
DOI: 10.21037/acs.2017.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of simultaneous septal myectomy and anterior mitral leaflet retention plasty in hypertrophic obstructive cardiomyopathy: the Berlin experience

Abstract: Background: Various surgical strategies designed to relieve left ventricular outflow tract obstruction (LVOTO) and correct mitral regurgitation (MR) in hypertrophic obstructive cardiomyopathy (HOCM) have evolved, yet reports on the long-term outcomes of each technique are scarce. We provide an update on over 20 years' experience at our institution in the standardized surgical treatment of HOCM. (median 12, range 1-23.2 years), MR was trivial in 87% and SAM was non-existent in all, outcomes that were maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…During follow up NYHA class reduced, the number of maintenance drugs decreased, reduction in LVOT gradient, and SAM was abolished. Two patients however needed immediate MV replacement due to severe residual MR post operatively 28 . Dulguerov et al performed SM followed by MV repair by increasing AML height and decreasing PML height.…”
Section: Surgical Myectomymentioning
confidence: 99%
“…During follow up NYHA class reduced, the number of maintenance drugs decreased, reduction in LVOT gradient, and SAM was abolished. Two patients however needed immediate MV replacement due to severe residual MR post operatively 28 . Dulguerov et al performed SM followed by MV repair by increasing AML height and decreasing PML height.…”
Section: Surgical Myectomymentioning
confidence: 99%
“…Изолированной МЭ зачастую недостаточно для полного устранения обструкции ВТЛЖ из-за сохраняющегося переднего систолического движения МК за счет изменения Результаты хирургического лечения ГКМП [33][34][35][36][37][38] Results of surgical treatment of HCM [33][34][35][36][37][38] Автор, клиника…”
Section: хирургическое лечениеunclassified
“…They concluded that ALRP sustained absence of SAM, absence of residual LVOT obstruction, and improvement in hemodynamic and functional statuses. 27) …”
Section: Introductionmentioning
confidence: 99%